A rapid and highly efficient method for transformation of sugarcane callus - Santosa, Dwi Andreas; Hendroko, Roy; Farouk, Abdelazim; Greiner, Ralf (Humana Press, 2004)

(untitled)
Modern sugarcane cultivars have complex genetic characteristics and low fertility that render their genetic improvement through traditional breeding difficult. Genetic engineering methodology to introduce foreign genes provides new opportunities for the genetic improvement of sugarcane cultivars. One of prerequisites for successful insertion of a gene cassette into the plant genome is the availability of an efficient transformation protocol. An improved protocol for Agrobacterium-mediated transformation of sugarcane is described. Between 85 and 100% of calli transformed using this procedure produced new calli, and 100% of them were positive for the inserted gene. The whole procedure permitted the production of transgenic calli in a short time (1.5 mo). The transformed calli can be cultured further for the production of the inserted gene-encoded enzyme by using cell culture, or they can be regenerated into transgenic plants. This protocol may be implemented also for the generation of transgenic plants from other species.